A Parting Note. (The Accounting Review, 1987)
The author offers his parting message as the book review editor of the journal "The Accounting Review." He expresses his gratitude to those who helped him as the book review editor. He relates the disappointments he experienced as the book review editor. A summary of Book Review Section activities from April 1984 to January 1987 is presented.